A multi-faceted approach to increase appropriate analgesia prescribing in the emergency department. Issue 1 (12th October 2015) - Ratneswaran, Culadeeban; Dodd, Kevin; Enright, Kevin; Dasan, Sunil
Abstract: Pain is the most common presenting complaint within the emergency department. Whilst national RCEM guidelines exist, there tends to be low compliance with its use. A retrospective, cross-sectional audit, over a 24 hour period, was carried out in the emergency department of a tertiary hospital in London on all patients with abdominal pain. Pain score documentation was checked as well as: whether analgesia prescribed was compliant with guidelines, time to prescription, and if pain scores were rechecked within an hour. Cycle 1 (21 patients) showed that only 29% of patients were prescribed analgesia in accordance with guidelines, 38% of pain scores were documented at triage, and only 19% of scores were rechecked at any time. 22% of patients in severe pain were prescribed analgesia within the recommended duration from presentation (20 minutes). New guidelines, adapted from RCEM, were departmentally approved and disseminated to reflect local medication use. Monthly doctor and nurse teaching sessions were established to improve guideline compliance, objective pain score documentation, and encourage results driven performance. A nurse prescriber champion was established to encourage analgesia prescribing competence in addressing delayed administration. Finally, plans to integrate electronic pain scoring with timer prompts for rechecking are in place to help streamline the process. Following these interventions, cycle 2 (n=23) showed 87% of pain scores were documented at triage, 52% were prescribed guideline concordant analgesia, and 40% of severe pain scores were acted upon in time. Cycle 3 (n=33) demonstrated the need for monthly educational intervention to maintain high standards; as in its absence, any improvement returned to baseline.